Electrochemical studies on the effect of residual stress on the corrosion of 316L manufactured by selective laser melting. (March 2020) - Cruz, V.; Chao, Q.; Birbilis, N.; Fabijanic, D.; Hodgson, P.D.; Thomas, S.
Highlights: Compressive residual stress reduced by 90% of the as-built value following 1100 °C for 5 min. Pitting potential decreased by around 180 mV on stress-relieving specimens. Repassivation potential increased with decreasing compressive stress for all specimens. Donor density in the passive film increased with decreasing compressive stress. Abstract: Selective Laser Melting (SLM) and various subsequent stress-relieving treatments were used to obtain 316 L specimens with compressive residual stresses, varying from 15 to 250 MPa. This enabled a study on the effect of residual stress on corrosion of 316 L using electrochemical methods, which is relevant for durability of additively manufactured materials. Overall, compressive stresses in SLM 316 L result in a measurable increase in the pitting potential, accompanied by a decrease in the passive film currents and donor densities. It is proposed that compressive stresses lower the film growth and repassivation kinetics but slightly enhances the pitting resistance of SLM 316 L.